INDEKS INOVASI DINAS KEPENDUDUKAN DAN CATATAN SIPIL DALAM PELAYANAN PEMBUATAN AKTA KELAHIRAN DI SUMBAWA - Ishak Rahman; Wahyu Haryadi; Sandy Alandari (Pusat Riset dan Publikasi, 2021)
The purpose of this study was to determine the innovation index of birth certificate making services implemented by the Department of Population and Civil Registration of Sumbawa Regency. The population in this study were all residents who carried out birth certificate making activities at the Population and Civil Registry Office of Sumbawa Regency. The sample of this study was determined based on the sampling formula from Krajcie and Roman. The number of samples in this study amounted to 66 people. The method used to collect data is by using a questionnaire. The data analysis technique used is the analysis of the innovation perception index based on the output aspect (newness dimension and productive dimension) and outcome aspect (impact dimension and sustainable dimension). The results showed that the innovation index in the output aspect scored